Comparative effectiveness of ustekinumab or vedolizumab after one year in 130 patients with anti‐TNF‐refractory Crohn's disease. Issue 8 (10th September 2020) - Townsend, Tristan; Razanskaite, Violeta; Dodd, Susanna; Storey, Daniel; Michail, Stephanie; Morgan, James; Davies, Michael; Penman, Douglas; Watters, Christopher; Swaminathan, Mira; Sabine, Joseph; Chapman, Adam; et al.
Summary: Background: Anti‐tumour necrosis factor (TNF) agents are effective in Crohn's disease but some patients lose response and require alternative biologic therapy. There are few data on comparative effectiveness of vedolizumab and ustekinumab in this setting. Aim: To compare the effectiveness of ustekinumab and vedolizumab in anti‐TNF‐refractory Crohn's disease over 12 months. Methods: Patients commencing ustekinumab or vedolizumab for anti‐TNF‐refractory Crohn's disease with minimum follow‐up of 12 months were included. The primary outcome measure was the difference in steroid‐free remission rates at end of induction (2 months) and at 12 months. We also assessed rates of clinical response and remission, treatment persistence, surgery and adverse events in both groups. We performed logistic regression analysis to assess factors associated with steroid‐free remission and clinical response and remission. Results: We included 85 patients commencing vedolizumab and 45 commencing ustekinumab. In an unadjusted model, rates of steroid‐free and clinical remission were significantly higher among ustekinumab‐treated patients. After adjusting for confounders, steroid‐free remission was higher among ustekinumab‐treated patients at 2 months (odds ratio, OR 2.79, 95% confidence interval, CI 1.06‐7.39, P = 0.038) and 12 months (OR 2.01, 95% CI 0.89‐4.56, P = 0.095). More patients treated with ustekinumab remained on therapy at the end of 12 months (84.4% vs 61.5%, P = 0.007). Conclusions: Ustekinumab appeared more effective in treating anti‐TNF‐refractory Crohn's disease and more patients persisted with therapy.